Teaching with the common core standards for English language arts, preK-2 - Morrow, Lesley Mandel; Shanahan, Timothy; Wixson, Karen K. (The Guilford Press, 2012)
"The Common Core State Standards (CCSS) are the first academic standards to be independently adopted by almost every state in the country. The purpose and intent of the Common Core standards for English Language Arts (ELA), as well as Literacy in History/Social Studies and Science Education, are the focus of this book. Each of the chapters addresses one of the major English Language Arts domains: literature, informational texts, foundational skills, writing, speaking and listening, language, technology, and assessment. The objective of the chapters is twofold: to provide a theoretical background and detailed explanation of each of the CCSS/ELA standards, as well as practical suggestions, classroom vignettes, models, instructional resources, and unit ideas to implement the standards"--